Restriction polymorphism maps of Neurospora crassa: 2000 update - Mary Anne Nelson; David D Perkins (Fungal Genetics Reports, 2000)
Restriction fragment length polymorphisms (RFLPs) can be used to determine the approximate map location of any cloned piece of DNA. To establish an RFLP mapping system for N. crassa, R.L. Metzenberg and coworkers crossed strains with multiple sequence differences, an Oak Ridge laboratory strain (designated "O") and a Mauriceville-1c wild-collected strain (designated "M"; Metzenberg et al. 1984 Neurospora Newsl. 31:35-39; ibid. 1985 Proc. Natl. Acad. Sci. U.S.A. 82:2067-2071; Metzenberg and Grotelueschen 1995 Fungal Genet. Newsl. 42:82-90). Progeny from two separate crosses have been widely distributed and used for mapping. For the first cross, 38 progeny from 18 ordered asci were analyzed. Because nonsister spores from the same half of the ascus were selected, first-division segregation can be distinguished from second-division. For the second cross 18 random ascospore progeny were analyzed. The first cross is preferred for RFLP mapping, for several reasons: resolution is better because more loci have been scored; distance from the centromere can be estimated regardless of which linkage group is involved; double crossovers within intervals can be recognized, as can putative gene conversions or scoring errors.However, updated maps for both crosses are presented here.